Pay Equity, Discrimination and Undervaluation - Dick, Christian (My University, 1987)
Comparable worth legislation is designed to remedy what its proponents perceive to be the systematic and entrenched under-valuation of the labour of those who work in occupations in which women predominate. Comparable worth legislation would mandate equal pay for certain jobs within an establishment judged by some standard as of equivalent value, absent certain sanctioned exceptions. After outlining the major points at issue in the comparable worth debate, this thesis looks at the argument that current practice in labour markets engenders or perpetuates a discriminatory condition harmful to certain groups. It then argues that the conceptual heart of the pay equity advocacy is an attack on the market as a pricing vehicle in the name of a theory of distributive justice heavily reliant on the concept of desert.
Keywords: Political Science; Political Science